Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the given system of equations by elimination, follow these steps:
### Given Equations
1. [tex]\(-5x - 2y = -12\)[/tex] (Equation 1)
2. [tex]\(3x + 2y = 8\)[/tex] (Equation 2)
### Step 1: Add the equations
Notice that the coefficients of [tex]\(y\)[/tex] in both equations are opposites ([tex]\(-2\)[/tex] and [tex]\(2\)[/tex]), so adding the equations will eliminate [tex]\(y\)[/tex].
[tex]\[ \begin{array}{rl} (-5x - 2y) + (3x + 2y) &= -12 + 8 \\ -5x + 3x &= -4 \\ -2x &= -4 \\ x &= 2 \end{array} \][/tex]
### Step 2: Substitute the value of [tex]\(x\)[/tex] back into one of the original equations
Now that we have [tex]\(x = 2\)[/tex], we can substitute this value back into either Equation 1 or Equation 2 to solve for [tex]\(y\)[/tex]. Let's use Equation 2:
[tex]\[ 3x + 2y = 8 \\ 3(2) + 2y = 8 \\ 6 + 2y = 8 \\ 2y = 2 \\ y = 1 \][/tex]
### Step 3: Write the solution as an ordered pair
The solution to the system of equations is [tex]\((x, y) = (2, 1)\)[/tex].
So the ordered pair solution is [tex]\((2, 1)\)[/tex].
### Given Equations
1. [tex]\(-5x - 2y = -12\)[/tex] (Equation 1)
2. [tex]\(3x + 2y = 8\)[/tex] (Equation 2)
### Step 1: Add the equations
Notice that the coefficients of [tex]\(y\)[/tex] in both equations are opposites ([tex]\(-2\)[/tex] and [tex]\(2\)[/tex]), so adding the equations will eliminate [tex]\(y\)[/tex].
[tex]\[ \begin{array}{rl} (-5x - 2y) + (3x + 2y) &= -12 + 8 \\ -5x + 3x &= -4 \\ -2x &= -4 \\ x &= 2 \end{array} \][/tex]
### Step 2: Substitute the value of [tex]\(x\)[/tex] back into one of the original equations
Now that we have [tex]\(x = 2\)[/tex], we can substitute this value back into either Equation 1 or Equation 2 to solve for [tex]\(y\)[/tex]. Let's use Equation 2:
[tex]\[ 3x + 2y = 8 \\ 3(2) + 2y = 8 \\ 6 + 2y = 8 \\ 2y = 2 \\ y = 1 \][/tex]
### Step 3: Write the solution as an ordered pair
The solution to the system of equations is [tex]\((x, y) = (2, 1)\)[/tex].
So the ordered pair solution is [tex]\((2, 1)\)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.